Long-term effect of dietary fibre intake on glycosylated haemoglobin A1c level and glycaemic control status among Chinese patients with type 2 diabetes mellitus. Issue 8 (24th July 2013) - Yang, Luxi; Shu, Le; Jiang, Junyi; Qiu, Hua; Zhao, Genming; Zhou, Yi; Jiang, Qingwu; Sun, Qiao; Qin, Guoyou; Wu, Hongyan; Yang, Liming; Ruan, Xiaonan; et al.
Abstract: Objective: Dietary fibre has been linked to lower levels of glycosylated haemoglobin A1c (HbA1c) among diabetes patients. The present study aimed to evaluate the long-term effect of dietary fibre on HbA1c levels among Chinese patients with type 2 diabetes mellitus. Design: Two cross-sectional surveys were conducted in 2006 and 2011, with the second one being a repeat survey on a sub-sample from the initial one. In both surveys, an in-person interview was conducted to collect information on demographic characteristics and lifestyles following a similar protocol. Dietary intake was assessed with a validated FFQ. Anthropometric measures and biochemical assays were performed at the interview. Setting: Communities in Pudong New Area of Shanghai, China. Subjects: Chinese patients ( n 934) with type 2 diabetes mellitus. Results: An inverse association was observed between dietary fibre and glycaemic status indicated by HbA1c level in both surveys, although it was significant only in the first survey. Among 497 patients participating in both surveys, dietary fibre intake at the first survey was inversely associated with uncontrolled glycaemic status at the second survey, with adjusted odds ratios across the tertiles of intake being 1·00, 0·72 (95 % CI 0·43, 1·21) and 0·58 (95 % CI 0·34, 0·99; P trend = 0·048). The change in fibre intake was slightly associated with glycaemic status, with each increase in tertile scores of intake linked to a 0·138 % ( β = −0·138; 95 % CI −0·002, 0·278) decrease in HbA1c value and a 19 % (OR = 0·81; 95 % CI 0·65, 1·02) reduced risk of uncontrolled glycaemic status at the second survey. Conclusions: Dietary fibre may have a long-term beneficial effect on HbA1c level among Chinese diabetes patients.